Optimal. Leaf size=30 \[ 6 x+\log \left (\frac {1}{4} x^2 \left (5+5 \left (e^x-x+\left (e^x+x\right )^2\right )\right )\right ) \]
________________________________________________________________________________________
Rubi [F] time = 0.87, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {2+3 x-2 x^2+6 x^3+e^{2 x} (2+8 x)+e^x \left (2+13 x+14 x^2\right )}{x+e^{2 x} x-x^2+x^3+e^x \left (x+2 x^2\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left (\frac {2 (1+4 x)}{x}-\frac {3-e^x-4 x+2 e^x x+2 x^2}{1+e^x+e^{2 x}-x+2 e^x x+x^2}\right ) \, dx\\ &=2 \int \frac {1+4 x}{x} \, dx-\int \frac {3-e^x-4 x+2 e^x x+2 x^2}{1+e^x+e^{2 x}-x+2 e^x x+x^2} \, dx\\ &=2 \int \left (4+\frac {1}{x}\right ) \, dx-\int \left (\frac {3}{1+e^x+e^{2 x}-x+2 e^x x+x^2}-\frac {e^x}{1+e^x+e^{2 x}-x+2 e^x x+x^2}-\frac {4 x}{1+e^x+e^{2 x}-x+2 e^x x+x^2}+\frac {2 e^x x}{1+e^x+e^{2 x}-x+2 e^x x+x^2}+\frac {2 x^2}{1+e^x+e^{2 x}-x+2 e^x x+x^2}\right ) \, dx\\ &=8 x+2 \log (x)-2 \int \frac {e^x x}{1+e^x+e^{2 x}-x+2 e^x x+x^2} \, dx-2 \int \frac {x^2}{1+e^x+e^{2 x}-x+2 e^x x+x^2} \, dx-3 \int \frac {1}{1+e^x+e^{2 x}-x+2 e^x x+x^2} \, dx+4 \int \frac {x}{1+e^x+e^{2 x}-x+2 e^x x+x^2} \, dx+\int \frac {e^x}{1+e^x+e^{2 x}-x+2 e^x x+x^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.29, size = 31, normalized size = 1.03 \begin {gather*} 6 x+2 \log (x)+\log \left (1+e^x+e^{2 x}-x+2 e^x x+x^2\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.74, size = 29, normalized size = 0.97 \begin {gather*} 6 \, x + \log \left (x^{2} + {\left (2 \, x + 1\right )} e^{x} - x + e^{\left (2 \, x\right )} + 1\right ) + 2 \, \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.43, size = 28, normalized size = 0.93 \begin {gather*} 6 \, x + \log \left (x^{2} + 2 \, x e^{x} - x + e^{\left (2 \, x\right )} + e^{x} + 1\right ) + 2 \, \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.04, size = 29, normalized size = 0.97
method | result | size |
norman | \(6 x +2 \ln \relax (x )+\ln \left ({\mathrm e}^{2 x}+2 \,{\mathrm e}^{x} x +x^{2}+{\mathrm e}^{x}-x +1\right )\) | \(29\) |
risch | \(6 x +2 \ln \relax (x )+\ln \left ({\mathrm e}^{2 x}+\left (2 x +1\right ) {\mathrm e}^{x}+x^{2}-x +1\right )\) | \(30\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.43, size = 29, normalized size = 0.97 \begin {gather*} 6 \, x + \log \left (x^{2} + {\left (2 \, x + 1\right )} e^{x} - x + e^{\left (2 \, x\right )} + 1\right ) + 2 \, \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.15, size = 28, normalized size = 0.93 \begin {gather*} 6\,x+\ln \left ({\mathrm {e}}^{2\,x}-x+{\mathrm {e}}^x+2\,x\,{\mathrm {e}}^x+x^2+1\right )+2\,\ln \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.16, size = 29, normalized size = 0.97 \begin {gather*} 6 x + 2 \log {\relax (x )} + \log {\left (x^{2} - x + \left (2 x + 1\right ) e^{x} + e^{2 x} + 1 \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________